2022
DOI: 10.3390/buildings12050522
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Barriers and Motivators for the Adoption of Base Isolation Systems in New Zealand

Abstract: A base isolator is a proven system that can significantly reduce any damage to a building in the event of an earthquake. Despite their efficacy, seismic isolators are not widely used in New Zealand, with only about forty systems in use during the 2010 and 2011 Canterbury Earthquakes. This study seeks to investigate why base isolation systems are not frequently used in seismic strengthening projects and buildings in New Zealand. It also focuses on determining ways in which seismic isolators could become more wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Moreover, these researchers pointed out that for the actual cost comparison, it is necessary to assess the conventional and isolated structures under the same performance criteria. In one example, where both the conventional and isolated structures are evaluated under the same performance level, the isolation cost was reduced by 6% [158]. A recent study by Egbelakin et al [158] identified the hurdles in implementing base isolation strategies.…”
Section: Challenges In the Worldwide Implementation Of Isolation Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these researchers pointed out that for the actual cost comparison, it is necessary to assess the conventional and isolated structures under the same performance criteria. In one example, where both the conventional and isolated structures are evaluated under the same performance level, the isolation cost was reduced by 6% [158]. A recent study by Egbelakin et al [158] identified the hurdles in implementing base isolation strategies.…”
Section: Challenges In the Worldwide Implementation Of Isolation Schemesmentioning
confidence: 99%
“…In one example, where both the conventional and isolated structures are evaluated under the same performance level, the isolation cost was reduced by 6% [158]. A recent study by Egbelakin et al [158] identified the hurdles in implementing base isolation strategies. Although the researchers discussed the context of the implementation scenario in New Zealand, most of the addressed issues are common in many developing countries.…”
Section: Challenges In the Worldwide Implementation Of Isolation Schemesmentioning
confidence: 99%